2020
DOI: 10.1038/s41598-020-66962-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an antioxidant supplement containing high dose lutein and zeaxanthin on macular pigment and skin carotenoid levels

Abstract: The effect of a high dose lutein/zeaxanthin supplement on macular pigment optical density (MPOD) and skin carotenoid (SC) levels in healthy subjects was investigated. This is a prospective, single-arm, open-label study. Subjects were 16 Japanese, age 26-57 years. Subjects took a supplement containing 20 mg/day of lutein, 4 mg/day of zeaxanthin, and other antioxidants (vitamin C, vitamin E, zinc, copper) for 16 weeks. MPOD levels were measured by a two-wavelength autofluorescence imaging technique. SC levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 56 publications
(58 reference statements)
3
20
0
Order By: Relevance
“…Previous work has shown that the total carotenoid content in skin and blood is associated with macular pigment carotenoid accumulation 24 . In the current trial, goji berry intake was signi cantly associated with the skin carotenoid score, which is consistent with the recent observation by Obana et al who reported a signi cant increase in skin carotenoid levels following the intake of 20 mg of L and 4 mg of Z along with modest amounts of vitamins and minerals for 16 weeks 25 . Improvements in macular pigment optical volume and MPOD for those with a BMI < 25 kg/m 2 were also reported 25 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous work has shown that the total carotenoid content in skin and blood is associated with macular pigment carotenoid accumulation 24 . In the current trial, goji berry intake was signi cantly associated with the skin carotenoid score, which is consistent with the recent observation by Obana et al who reported a signi cant increase in skin carotenoid levels following the intake of 20 mg of L and 4 mg of Z along with modest amounts of vitamins and minerals for 16 weeks 25 . Improvements in macular pigment optical volume and MPOD for those with a BMI < 25 kg/m 2 were also reported 25 .…”
Section: Discussionsupporting
confidence: 92%
“…In the current trial, goji berry intake was signi cantly associated with the skin carotenoid score, which is consistent with the recent observation by Obana et al who reported a signi cant increase in skin carotenoid levels following the intake of 20 mg of L and 4 mg of Z along with modest amounts of vitamins and minerals for 16 weeks 25 . Improvements in macular pigment optical volume and MPOD for those with a BMI < 25 kg/m 2 were also reported 25 . We did not collect BMI data in the current trial, so we are unable to assess the impact of BMI on MPOD and skin carotenoid score.…”
Section: Discussionsupporting
confidence: 92%
“…Some participants had a VM score of zero. It is likely that participants with low dermal carotenoid levels also had low macular pigment levels and potentially resulting vision disorders [63,64]. Validating low scores, for example, by assessing eye function or screening for vision disorders, is therefore recommended.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…Known confounders, such as BMI, smoking status, and diabetes, were often not controlled for or reported on in the studies. BMI was reported in 31 studies ( 7–9 , 11 , 12 , 25–35 , 40 , 42–44 , 46–49 , 53 , 56 , 57 , 59 , 60 , 63 ), smoking status was reported in 26 studies ( 8 , 9 , 12 , 25 , 27 , 29–32 , 34–36 , 40 , 42–44 , 46–50 , 54 , 59 , 60 , 63 , 64 ), and diabetes was reported in 10 studies ( 25 , 30 , 38 , 40 , 42 , 49 , 57 , 59 , 63 , 64 ).…”
Section: Resultsmentioning
confidence: 99%